2021
DOI: 10.1021/acs.biochem.1c00063
|View full text |Cite
|
Sign up to set email alerts
|

Caught in Action: X-ray Structure of Thymidylate Synthase with Noncovalent Intermediate Analog

Abstract: Methylation of 2-deoxyuridine-5ʹ-monophosphate (dUMP) at the C5 position by the obligate dimeric thymidylate synthase (TSase) in the sole de novo biosynthetic pathway to dTMP proceeds by forming a covalent ternary complex with dUMP and co-substrate 5,10methylenetetrahydrofolate. The crystal structure of an analog of this intermediate gives important mechanistic insights but does not explain the half-of-the sites activity of the enzyme. Recent experiments showed that the C5 proton and the catalytic Cys are elim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The ligand-induced conformational change upon CHO-H 4 folate and its noncompetitive inhibition in the NADH:menadione oxidoreductase assay were unexpected, as the change in dimer interface (dimer mode 1) is less extensive (than dimer mode 2); crystallographic evidence shows that CHO-H 4 folate is found only in the active site. Several other folate-binding enzymes, namely DHFR ( 18 ) and TYMS ( 31 , 32 ), have shown that protein motions, in the form of conformational sampling in the active site (DHFR) or the existence of conformational ensembles (both) are crucial not only to catalysis but represent a route through which allostery can emerge. In the case of TYMS, the existence of a ligand-induced β-kink in the dimer interface directly couples the active sites between monomers and explains its observed half-sites reactivity ( 31 ), with an asymmetric dimer assembly structure elucidated ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ligand-induced conformational change upon CHO-H 4 folate and its noncompetitive inhibition in the NADH:menadione oxidoreductase assay were unexpected, as the change in dimer interface (dimer mode 1) is less extensive (than dimer mode 2); crystallographic evidence shows that CHO-H 4 folate is found only in the active site. Several other folate-binding enzymes, namely DHFR ( 18 ) and TYMS ( 31 , 32 ), have shown that protein motions, in the form of conformational sampling in the active site (DHFR) or the existence of conformational ensembles (both) are crucial not only to catalysis but represent a route through which allostery can emerge. In the case of TYMS, the existence of a ligand-induced β-kink in the dimer interface directly couples the active sites between monomers and explains its observed half-sites reactivity ( 31 ), with an asymmetric dimer assembly structure elucidated ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several other folate-binding enzymes, namely DHFR ( 18 ) and TYMS ( 31 , 32 ), have shown that protein motions, in the form of conformational sampling in the active site (DHFR) or the existence of conformational ensembles (both) are crucial not only to catalysis but represent a route through which allostery can emerge. In the case of TYMS, the existence of a ligand-induced β-kink in the dimer interface directly couples the active sites between monomers and explains its observed half-sites reactivity ( 31 ), with an asymmetric dimer assembly structure elucidated ( 32 ). More studies are necessary to determine how noncompetitive inhibition in tMTHFR occurs and could prove invaluable in delineating the catalytic cycle of MTHFR itself.…”
Section: Discussionmentioning
confidence: 99%